Dominant source of disorder in graphene: charged impurities or ripples?. (11th January 2017) - Fan, Zheyong; Uppstu, Andreas; Harju, Ari
Abstract: Experimentally produced graphene sheets exhibit a wide range of mobility values. Both extrinsic charged impurities and intrinsic ripples (corrugations) have been suggested to induce long-range disorder in graphene and could be a candidate for the dominant source of disorder. Here, using large-scale molecular dynamics and quantum transport simulations, we find that the hopping disorder and the gauge and scalar potentials induced by the ripples are short-ranged, in strong contrast with predictions by continuous models, and the transport fingerprints of the ripple disorder are very different from those of charged impurities. We conclude that charged impurities are the dominant source of disorder in most graphene samples, whereas scattering by ripples is mainly relevant in the high carrier density limit of ultraclean graphene samples (with a charged impurity concentration less than about 10 ppm) at room and higher temperatures. Our finding is valuable to theoretical modelling of transport properties of not only graphene, but also other two-dimensional materials, as the thermal ripples are universal.